Knowledge, Attitude, And Practice On Cervical Cancer And Hpv Vaccination Among Active Female Clinical Students In Faculty Of Medicine Universitas Pelita Harapan And In Correlation With Obstetric And Gynecology Rotation - Julita D.L. Nainggolan; Celine Chrystelle; Chintya Marcellin; Ongky Satria (Syntax Corporation Indonesia, 2024)
In 2018, the global prevalence of Human Papillomavirus (HPV) infections reached approximately 43 million cases, with cervical cancer attributed to 75% of cases in women. The HPV vaccine has shown efficacy in preventing up to 88% of cervical cancer cases. To address the lack of awareness surrounding HPV and cervical cancer prevention, this study aimed to assess the knowledge, attitude, and practice among active female medical students at the Faculty of Medicine, Universitas Pelita Harapan. In March 2023, this cross-sectional study utilized a questionnaire developed and validated by Winarto et al., covering socio-demographic information and questions related to cervical cancer. Out of 168 participants, 75.6% demonstrated good knowledge about cervical cancer, yet the practice of raising awareness and HPV vaccination was notably low. Interestingly, students who underwent obstetric and gynecology rotations exhibited similar low practice scores (87.5%) compared to those who had not. Furthermore, only 40% of students had completed their HPV vaccination. The study suggests a disconnect between knowledge, attitude, and practice among students, with no significant influence observed from obstetric and gynecology rotations.